Transcription Factor VviMYB86 Oppositely Regulates Proanthocyanidin and Anthocyanin Biosynthesis in Grape Berries - Cheng, Jing; Yu, Keji; Shi, Ying; Wang, Jun; Duan, Changqing (Frontiers in Plant Science, 2021)
Proanthocyanidins (PAs) and anthocyanins are two vital groups of flavonoid compounds for grape berries and red wines. Several transcription factors (TFs) have been identified to be involved in regulating PA and anthocyanin biosynthesis in grape berries. However, research on TFs with different regulatory mechanisms for these two biosynthesis branches in grapes remains limited. In this study, we identified an R2R3-MYB TF, VviMYB86, whose spatiotemporal gene expression pattern in grape berries coincided well with PA accumulation but contrasted with anthocyanin synthesis. Both in vivo and in vitro experiments verified that VviMYB86 positively regulated PA biosynthesis, primarily by upregulating the expression of the two leucoanthocyanidin reductase (LAR) genes in the Arabidopsis protoplast system, as well as in VviMYB86-overexpressing grape callus cultured under 24 h of darkness. Moreover, VviMYB86 was observed to repress the anthocyanin biosynthesis branch in grapes by downregulating the transcript levels of VviANS and VviUFGT. Overall, VviMYB86 is indicated to have a broad effect on flavonoid synthesis in grape berries. The results of this study will help elucidate the regulatory mechanism governing the expression of the two LAR genes in grape berries and provide new insights into the regulation of PA and anthocyanin biosynthesis in grape berries.